Mucoadhesive Film for Local Delivery to Oral Cancer: Formulation Development, Box–Behnken Experimental Design, and In vitro Characterization - Soni, Vandana (Asian Journal of Pharmaceutics (AJP), 2022)
Background: Oral cancer affects millions of people worldwide, which is more common in those 35 and older. Low-targeted therapy options for oral malignancies and poor drug uptake by lesions in the oral cavity followed by systemic injection contribute to high mortality and poor patient quality of life. Aim: The present study was undertaken for optimization and assessment of the designed cisplatin mucoadhesive film made of hydroxyl propyl methyl cellulose and chitosan that can be used locally to treat oral cancer. Materials and Methods: The films were prepared by solvent casting method, employing a Box–Behnken design, and subsequently confirmed by ANOVA analysis. The formulations were optimized by swelling index and residence time. Physiochemical characteristics of oral films, including pH, weight, thickness, tensile strength, folding endurance, and in vitro drug release, were also assessed. Results and Discussion: According to the factors selected for the optimization, the formulation (F3) was selected as the optimized formulation with highest desirability of 0.997. In vitro release profile indicated initial burst release and subsequently a sustained release of cisplatin from the film for 24 h. The release kinetics data displayed a Korsmeyer–Peppas release model with the best-fit match R2 value (0.9257). In vitro exposing the KB-3-1 cell line to the optimized film resulted in dose-dependent cancer cell death. The IC50 of free cisplatin and cisplatin mucoadhesive film (F3) on KB-3-1 was found to be 94.25 μg/ml and 23.64 μg/ml, respectively. This study demonstrates that local bioadhesive therapies are effective in treating cancer of the oral cavity. Conclusion: On the basis of data, it could be concluded that the number of polymers used was the critical factor for the production of cisplatin mucoadhesive film that had a substantial influence on their physical attributes. This factorial design study has served as a valuable tool for optimizing mucoadhesive film for the delivery of cisplatin.